Cytoplasmic and nuclear HER4 expression in HER2 negative breast cancer cell lines - Siti Norasikin Mohd Nafi,; Nursyazana Aqilah Ali, (Penerbit Universiti Kebangsaan Malaysia, 2022)
HER4 cleavage and its subcellular localisations have been previously proven to mediate anti-HER2 resistance. The description of the HER4 subcellular localisations in HER2 negative breast cancer, on the other hand, is incomplete. The objective of this study was to determine the cytoplasmic and nuclear expression of HER4 in HER2 negative breast cancer cell lines in order to gain a better understanding of the key features of HER4 signalling in the context of anti-HER2 resistance. MCF-7 and MDA-MB-231 cells were cultured for 48 h at 37 °C and 5% CO2 in fresh DMEM medium with 10% foetal bovine serum and 1% penicillin-streptomycin. The western blot analysis for HER4 protein was done on cytoplasmic and nuclear extracts that had been obtained previously using the NE-PER Nuclear and Cytoplasmic Extraction Kit. Cytoplasmic and nuclear HER4 proteins were expressed in a variety of sizes, including 120 kDa, 55 kDa, 50 kDa, and 43 kDa. MCF-7 cells expressed significantly more cytoplasmic HER4120kDa than MDA-MB-231 cells. MCF-7 exhibited a single nuclear HER4 variant with a molecular weight of 50 kDa, whereas MDA-MB-231 expressed two nuclear HER4 variants with molecular weights of 50 kDa and 43 kDa. In comparison to MDA-MB-231 cells, MCF-7 cells exhibit higher level of cytoplasmic HER4120kDa with positive nuclear HER450kDa expression. Due to the presence of ER and PR in MCF-7, it is important to investigate if the interaction of these HER4 variants with ER and PR confers resistance to anti-HER2 treatment on breast cancer. Meanwhile, results from MDA-MB-231 cells indicate that nuclear HER4 contributes to the development of TNBC.